2022
DOI: 10.1002/pc.26731
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study on the predicted fiber orientation of large area extrusion deposition additive manufactured composites

Abstract: The recent‐emerging Large Area extrusion deposition Additive Manufacturing (LAAM) provides a low‐cost and high‐efficient alternative manufacturing approach for industries like automotive and aerospace. Fiber orientation information significantly determines the material performances of LAAM‐produced short fiber reinforced composites. Numerical studies have been performed to better understand the microstructural formation of the fiber orientation in deposited beads. The fully coupled flow/orientation analysis ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(86 reference statements)
1
2
0
Order By: Relevance
“…Lately, Wang integrated the fullycoupled flow/orientation analysis approach with the sophisticated pARD-RSC fiber orientation prediction model. 24 At the starting condition of 3D-random fiber orientation at nozzle entry, the predicted values of fiber orientation demonstrated good consistency with data from previous experiments. 10 It is widely accepted that the macro anisotropic behavior of the created composites is directly influenced by the fiber orientation within the deposited beads.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Lately, Wang integrated the fullycoupled flow/orientation analysis approach with the sophisticated pARD-RSC fiber orientation prediction model. 24 At the starting condition of 3D-random fiber orientation at nozzle entry, the predicted values of fiber orientation demonstrated good consistency with data from previous experiments. 10 It is widely accepted that the macro anisotropic behavior of the created composites is directly influenced by the fiber orientation within the deposited beads.…”
Section: Introductionsupporting
confidence: 79%
“…A prior study pointed out the importance of the initial fiber orientation assumption on the final predicted fiber orientation in the flow end. 45 In one of our companion works, 24 we showed that the three-dimensional (3D) isotropic fiber orientation state (cf. Figure 4) assumed in the flow inlet resulted in predicted fiber orientation results in line with related experimental work.…”
Section: Fiber Orientation Predictionmentioning
confidence: 99%
“…Polymer composites reinforced with natural fibers are partially biodegradable and possess advantageous qualities such as minimum weight, comparable specific strength, and economical aspects. 1 These aspects of environmentfriendly natural fiber amalgamated polymer composites have made it a choice of material in the aerospace and automobile industries. 2,3 Natural fiber-reinforced polymer composites offer opportunities to replace synthetic fibers derived from crude oil by-products in composite industries.…”
Section: Introductionmentioning
confidence: 99%